Apex court flip flop on basic structure doctrine: a review of Maria Chin v director general of immigration [2021] 1 MLJ 750 - Ali Mohamed, Ashgar Ali; Ramalingam, Chithra Latha; Ahmad, Muhamad Hassan (2021)
This paper examines the recent Federal Court's decision in Maria Chin v Director General Of Immigration [2021] 1 MLJ 750